DISASTER RISK REDUCTION MELALUI ANALISIS DETEKSI WILAYAH RAWAN BANJIR DI REJOSO MENGGUNAKAN METODE FUZZY SUGENO - Cahya Mar'a Saliha Sumantri; Nur Amalia; Roudhatul Hikmawati; Safira Damayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2024)
Rejoso River is the largest in the Rejoso District (Pasuruan Regency, East Java). It often floods Rejoso District villages during the rainy season, so it must be managed thoroughly before, during, and after it hits Rejoso District. Disaster management needs to be carried out in a planned, integrated, coordinated, and comprehensive manner to protect the community and the threats, risks, and impacts of disasters. The type of research used in this study is an experiment aimed at building a decision support system in determining the villages most affected by flooding in the Rejoso District area. One of the efforts to prevent and reduce the impact of flood disasters is to provide information on flood-prone areas packaged in the form of digital maps. In order to find out the area in Rejoso District, Pasuruan Regency which is included in the flood-affected villages, a study was conducted using the mathematical method of Fuzzy Sugeno with the final results of a decision-making support system to be able to determine the area or villages in Rejoso District that were affected by the flood. The results showed that the Fuzzy Sugeno method gave the final decision, namely Kedungbako village as a village that was determined to be safe from floods and Manikrejo village was determined as a village affected by floods.